2014
DOI: 10.1111/ijfs.12625
|View full text |Cite
|
Sign up to set email alerts
|

Valorisation of theanine from decaffeinated tea dust in bakery functional food

Abstract: Nowadays, consumers appreciate the positive properties of decaffeinated tea for their well-being. During decaffeination process, a very fine tea dust powder is obtained as by-product, which contains the same quantity of bioactives as decaffeinated tea: the antioxidant polyphenols and the amino acid theanine. The aim was to add value to theanine gained from black tea powder dust and to develop theanine-enriched bread. A theanine containing powder was obtained by column separation of decaffeinated tea dust extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Wang and Zhou [36] reported that around 84% of the green tea catechins were retained in bread after baking. Also, theanine fortified breads lost up to 30% of theanine content after baking [16]. In this study, after baking, breads contained around 34% lower level of TPC than the corresponding dough.…”
Section: Bread Characteristicsmentioning
confidence: 48%
See 2 more Smart Citations
“…Wang and Zhou [36] reported that around 84% of the green tea catechins were retained in bread after baking. Also, theanine fortified breads lost up to 30% of theanine content after baking [16]. In this study, after baking, breads contained around 34% lower level of TPC than the corresponding dough.…”
Section: Bread Characteristicsmentioning
confidence: 48%
“…Aqueous tea fractions, theanine (T) and polyphenols (P) enriched fraction, respectively, were prepared from decaffeinated black tea dust, by fractionation on a XAD-16 resin, as reported in previous studies [16,17]. T fraction contained all free amino acids present in tea (among them, theanine with a content of 1.6 mg/mL), sugars (sucrose 1.4 mg/mL, glucose 5.3 mg/mL, fructose 4.7 mg/mL) and very polar phenolic compounds such as gallic acid (1 mg/mL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the use of instant tea (i.e. both to make tea and as a food ingredient) has become more accepted by consumers and has been widely applied in the food industry . Instant dark teas are made by drying the infusions of dark tea that had been processed via solid‐state fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…both to make tea and as a food ingredient) has become more accepted by consumers and has been widely applied in the food industry. 16,17 Instant dark teas are made by drying the infusions of dark tea that had been processed via solid-state fermentation. Lu et al 11 reported a new method of producing instant dark tea (Fu-brick) from green tea leaves processed by the fungus Eurotium cristatum using SF.…”
Section: Introductionmentioning
confidence: 99%